High involvement management and employee well-being - Petri Böckerman (IZA World of Labor, 2015)
A wide range of high involvement management practices, such as self-managed teams, incentive pay schemes, and employer-provided training have been shown to boost firms' productivity and financial performance. However, less is known about whether these practices, which give employees more discretion and autonomy, also benefit employees. Recent empirical research that aims to account for employee self-selection into firms that apply these practices finds generally positive effects on employee health and other important aspects of well-being at work. However, the effects can differ in different institutional settings.
Keywords: I10; J28; J81; M52; M53; M54; 330; high involvement management; employee well-being; job satisfaction; job quality